Thermal characterization of an ultrasonic measurement cell - Higuti, R. T.; Galindo, B. S.; Marçal, L. A.P.; Kitano, C.; Buiochi, F.; Adamowski, J. C. (My University, 2005)
Temperature plays an important role in any sensor device, because it can affect sensor properties, limiting its accuracy and operation range. At constant temperature, ultrasonic density sensors can reach accuracies of 0.1%. However, temperature fluctuations are expected to exist in an industrial plant, and sensor performance must be studied in the presence of temperature gradients. Each sensor geometry and construction can give rise to different behaviors under temperature gradients, limiting the possible accuracy in density measurements. In this work, an ultrasonic density measurement cell is experimentally characterized and its performance in the presence of temperature gradients is studied in the 15 to 40°C temperature range for several liquids. The propagation velocity can be measured with high accuracy (0.07%) in a range of temperatures as long as the sample chamber length is corrected. The cell was tested with distilled water, alcohol and other liquids, showing a 0.2% accuracy in density measurement for stabilized temperature and 0.4% under thermal gradient conditions. © 2005 IEEE.
Keywords: Liquids; Temperature characterization; Ultrasonic cell